Low Levels of Human Antibodies to Gametocyte-Infected Erythrocytes Contrasts the PfEMP1-Dominant Response to Asexual Stages in P. falciparum Malaria - Chan, Jo-Anne; Drew, Damien R.; Reiling, Linda; Lisboa-Pinto, Ashley; Dinko, Bismarck; Sutherland, Colin J.; Dent, Arlene E.; Chelimo, Kiprotich; Kazura, James W.; Boyle, Michelle J.; Beeson, James G. (Frontiers in Immunology, 2019)
Vaccines that target Plasmodium falciparum gametocytes have the potential to reduce malaria transmission and are thus attractive targets for malaria control. However, very little is known about human immune responses to gametocytes present in human hosts. We evaluated naturally-acquired antibodies to gametocyte-infected erythrocytes (gametocyte-IEs) of different developmental stages compared to other asexual parasite stages among naturally-exposed Kenyan residents. We found that acquired antibodies strongly recognized the surface of mature asexual-IEs, but there was limited reactivity to the surface of gametocyte-IEs of different stages. We used genetically-modified P. falciparum with suppressed expression of PfEMP1, the major surface antigen of asexual-stage IEs, to demonstrate that PfEMP1 is a dominant target of antibodies to asexual-IEs, in contrast to gametocyte-IEs. Antibody reactivity to gametocyte-IEs was similar to asexual-IEs lacking PfEMP1. Significant antibody reactivity to the surface of gametocytes was observed when outside of the host erythrocyte, including recognition of the major gametocyte antigen, Pfs230. This indicates that there is a deficiency of acquired antibodies to gametocyte-IEs despite the acquisition of antibodies to gametocyte antigens and asexual IEs. Our findings suggest that the acquisition of substantial immunity to the surface of gametocyte-IEs is limited, which may facilitate immune evasion to enable malaria transmission even in the face of substantial host immunity to malaria. Further studies are needed to understand the basis for the limited acquisition of antibodies to gametocytes and whether vaccine strategies can generate substantial immunity.